Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan pada PT PLN Indonesia Power UBP Mahakam - Setiawan, Ridho Eka; Hadiyanti , Sofia Ulfa Eka; Askiah , Askiah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to assess the extent to which work discipline influences employee performance at PT PLN Indonesia Power UBP Mahakam. Work discipline is considered a vital component that directly affects workforce efficiency and productivity within an organization. The study applies a quantitative approach using a survey method, in which questionnaires were distributed to all 50 active employees at the unit. Data were analyzed through simple linear regression with the assistance of SPSS version 25. The findings reveal a significant relationship between work discipline and employee performance, indicated by a regression coefficient of 0.431 and a significance value of 0.031 (< 0.05). This suggests that higher levels of discipline reflected in compliance with regulations, punctuality, and accountability are associated with improved employee performance. Elements such as professional behavior, commitment to working hours, and consistent task execution contribute positively to overall productivity. These results are in line with prior studies emphasizing that discipline is a key factor in achieving organizational success and operational effectiveness.